Microbial genetic composition regulates host social behavior - Ruijie Bai; Tao Wang; Rongrong Gu; Yawei Cai; Juntao Chen; Wen Cai; Dianshuang Zhou; Ying Li; Jixun Luo; Xiangming Wang; Zuobin Zhu (Gut Microbes, 2025)
The co-evolutionary relationship between gut microbiota and their hosts is influenced by microbial genetic variation, which enables adaptation to host environmental changes, modifies metabolic processes, and refines host–microbiota interactions. Investigating how gut microbial genetic variations influence host neurobehavior can provide insights into the pathogenesis of neurological disorders. In this study, we screened a comprehensive single-gene knockout library of Escherichia coli (E. coli) and identified 370 mutant strains that reduced social behavior in Caenorhabditis elegans (C. elegans). Notably, five mutations in the L-tyrosine biosynthesis pathway significantly alter the social aggregation behavior of C. elegans via the TGF-β signaling pathway. These findings highlight the importance of considering both microbial genetic variation and community composition in the examination of gut microbe-host neurobehavioral interactions. The establishment of this relationship provides a reference and experimental basis for the development of genetically engineered probiotics aimed at regulating host behavior.